Between the valley and the hill top. Discoursing on the spatial importance of Pego’s Bronze Age necropolis, Braga (Northwest of Portugal) - Bettencourt, Ana M. S. (2014)
This work reports the data which has been recovered from the excavation of Sector II of Pego. Among other kinds of evidence, that area encompasses traces of funerary practices dating back to the Bronze Age. Based upon the local’s choice, the structures’ architectonic features, their interrelations, materials associated and strati-graphy and in the carbon dating results available we have proposed different uses and occupation phases. Although certain materials reflect human presence during later periods, the frequency of that area denounce three occu-pation moments datable from between the Middle Bronze Age and the Late Bronze Age. These moments are consistent with the construction of a plain grave’s necropolis, probably forming familiar clusters, a hypothetic pits’ necropolis and, prior to the abandonment of the area, an “enclosure”. Given the interpretations presented we have discussed the possible relation between the local, certain physical charac-teristics and the presence of funerary practices. As a work hypothesis we consider those relations as fundamental for the places’ choice. Alongside with other evidence of difficult interpretation and, perhaps, in the context of new senses meanwhile acquired by this place, these data form part of this place’s biography.